Perancangan Strategi Re-Branding Sebagai Upaya Peningkatan Brand Image Mamah Factory Melalui Pemasaran Digital - Nainggolan, Ferdinand; Anggraini, Ratih; Kho, Karen; Ariyanto, Hepy Hefri; Hasan, Golan (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mamah Factory is a specialty souvenir center in Batam, featuring its signature products such as Luti Gendang, Kue Lapis Emas, Pancake Durian, Kue Emas Durian Keju, and Brownies Durian. In order to build a positive and healthy brand image for Mamah Factory, the author employed data collection methods including observation, interviews, documentation, and surveys to identify the uniqueness and differences of Mamah's products compared to others. The results of this Community Service activity brought in more viewers, followers, and buyers with content emphasizing Mamah's product values. The number of profile visits was higher compared to previous Community Service activities, with an increase in followers by 43, surpassing the 30-follower increase from the previous Community Service. In the next program, it is hoped that there will be improvements in all aspects that can help the community to better understand Mamah Factory in terms of its product values and quality.